Equivalent Activities of Repulsive Axon Guidance Receptors. - Long, H.; Yoshikawa, S.; Thomas, J.B. (Journal of Neuroscience, 2016)
Receptors on the growth cone at the leading edge of elongating axons play critical guidance roles by recognizing cues via their extracellular domains and transducing signals via their intracellular domains, resulting in changes in direction of growth. An important concept to have emerged in the axon guidance field is the importance of repulsion as a major guidance mechanism. Given the number and variety of different repulsive receptors, it is generally thought that there are likely to be qualitative differences in the signals they transduce. However, the nature of these possible differences is unknown. By creating chimeras using the extracellular and intracellular domains of three different Drosophila repulsive receptors, Unc5, Roundabout (Robo), and Derailed (Drl) and expressing them in defined cells within the embryonic nervous system, we examined the responses elicited by their intracellular domains systematically. Surprisingly, we found no qualitative differences in growth cone response or axon growth, suggesting that, despite their highly diverged sequences, each intracellular domain elicits repulsion via a common pathway. In terms of the signaling pathway(s) used by the repulsive receptors, mutations in the guanine nucleotide exchange factor Trio strongly enhance the repulsive activity of all three intracellular domains, suggesting that repulsion by Unc5, Robo, and Drl, and perhaps repulsion in general, involves Trio activity. A prevailing concept that has emerged in the axon guidance field is the importance of repulsion as a guidance mechanism for steering axons to their appropriate targets. Given the number and variety of different repulsive receptors, it is generally thought that there are differences in the signals that they transduce. However, this has never been tested directly. We have used the advanced genetics of Drosophila to compare directly the outputs of different repulsive receptors. Surprisingly, we found no qualitative differences in receptor-mediated repulsion, suggesting that, despite their highly diverged domain structure, each receptor couples to a common repulsive pathway. We went on to show that this common pathway involves Trio, a guanine nucleotide exchange factor known to promote cytoskeletal remodeling.